Proceedings of the 4th Annual International Seminar on Transformative Education and Educational Leadership (AISTEEL 2019) 2019
DOI: 10.2991/aisteel-19.2019.98
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Locus of Control, Work Environment, and Innovative Behavior on Teachers Work Commitment

Abstract: This study aims to determine the effect of locus of control on innovative behavior, the effect of the work environment on innovative behavior, the effect of locus of control on work commitment, the effect of the work environment on work commitment and the effect of innovative behavior on teachers work commitment. This study used path analysis with 161 teachers as research respondents. The sampling technique using Proportional Random Sampling. Before testing the hypothesis, the analysis requirements are tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Innovative behavior is a predictor of substantial corporate commitment, according to Agarwala's (2003) research. According to Pasaribu et al (2019), and the study's findings, their workplace culture significantly influences junior high school (SMP) instructors' job behavior. The research findings contradict the results of a survey by Akhtar et al (2019), demonstrating that affective commitment, perceived organizational support, and confidence indirectly impact the connection between person-organization fit and innovative work behavior.…”
Section: The Relationship Of Islamic Work Ethics To Teacher Work Comm...mentioning
confidence: 99%
See 1 more Smart Citation
“…Innovative behavior is a predictor of substantial corporate commitment, according to Agarwala's (2003) research. According to Pasaribu et al (2019), and the study's findings, their workplace culture significantly influences junior high school (SMP) instructors' job behavior. The research findings contradict the results of a survey by Akhtar et al (2019), demonstrating that affective commitment, perceived organizational support, and confidence indirectly impact the connection between person-organization fit and innovative work behavior.…”
Section: The Relationship Of Islamic Work Ethics To Teacher Work Comm...mentioning
confidence: 99%
“…2, March 2023, pages: 122-134 normative mindset that fosters interest in value-based commitment in early work in this area is based on a feeling of duty or accountability towards the goal and fulfilling the expectations of others(Somers et al, 2020).Innovative behavior is a predictor of substantial corporate commitment, according to a 2003 research by Agarwala. According toPasaribu et al (2019), and the study's findings, their workplace culture significantly influences junior high school (SMP) instructors' job behavior. The research's conclusions counter a study byAkhtar et al (2019), which found that emotional dedication, perceived organizational support, and confidence indirectly impact the link between person-organization fit and creative work behavior.…”
mentioning
confidence: 98%